Metastatic undifferentiated pleomorphic sarcoma diagnosed by endoscopic ultrasound‐guided fine‐needle aspiration. Issue 11 (3rd October 2022) - Hirao, Takeru; Ikezawa, Kenji; Takada, Ryoji; Otsuka, Tomoyuki; Korematsu, Mizuki; Nagata, Shigenori; Ohkawa, Kazuyoshi
Abstract : Pathological differentiation is important for suspected lesions of metastatic undifferentiated pleomorphic sarcoma (UPS) because no reliable imaging criteria exist for this entity yet. In the present case, transgastric endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA) for the pancreatic tumor and transcolonic EUS‐FNA for the intraabdominal tumor contributed to the definitive diagnosis of metastatic UPS, leading to appropriate treatment selection.